2015
DOI: 10.1111/ger.12183
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficiency of denture cleaners for removing denture adhesives

Abstract: Some denture cleaners could liquefy cream adhesives more than water, but these differences were not observed in case of powder and cushion adhesives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…8,20 According to Sato et al, 23 only brushing fails to promote adequate cleaning in all regions of the denture, which indicates the need to soak the denture in solutions of effervescent tablets. Harada-Hada et al 14 also observed that immersion in denture cleaning solutions could be an alternative method of denture adhesive removal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,20 According to Sato et al, 23 only brushing fails to promote adequate cleaning in all regions of the denture, which indicates the need to soak the denture in solutions of effervescent tablets. Harada-Hada et al 14 also observed that immersion in denture cleaning solutions could be an alternative method of denture adhesive removal.…”
Section: Discussionmentioning
confidence: 99%
“…Sato et al 23 investigated in vivo the ease of removing denture adhesives from the oral mucosa. Harada-Hada et al 14 investigated in vitro the efficiency of denture cleansers on adhesive removal and observed that some denture cleaners composed of enzymes and hydrogen peroxide could be indicated for the removal of cream-type adhesives.…”
mentioning
confidence: 99%
“…The experimental method used in this study is shown in Figures 1A-C. Experiments concerning the removal of denture adhesives were performed according to a previously described procedure [23,24], with modifications (Fig. 1A).…”
Section: Assay For Removal Of Denture Adhesives From Acrylic Resin Ma...mentioning
confidence: 99%
“…cient [23][24][25][26][27]. A study of immersion experiments revealed that commercial denture cleaners are suboptimal for daily use with respect to the removal of adhesives.…”
mentioning
confidence: 99%
See 1 more Smart Citation